PHOTOELECTRON-SPECTRA AND THEIR RELATIVISTIC INTERPRETATION FOR GASEOUS BISMUTH TRIHALIDES - Egdell, R; Hotokka, M; Laaksonen, L; Pyykko, P; Snijders, J (1982)
Photoelectron spectra are reported for BiCl3, BiBr3 and BiI3. Assignments are obtained using the relativistically parameterized extended Hückel (REX) and perturbative Hartree-Fock-Slater methods. The halogen p-bands (4a1, 1a2, 4e, and 3e) resemble those in the lighter MX3 molecules at (M = P- Sb). The bismuth-halogen sigma bond MOs (3a1 and 2e) suffer a relativistic rehybridization into e 1 2 > e 3 2 > e 1 2. © 1982.